2007
DOI: 10.1167/iovs.07-0266
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies of Antiglaucomatous Prostaglandin Analogues: Travoprost with and without Benzalkonium Chloride and Preserved Latanoprost

Abstract: Latanoprost with BAK, travoprost with BAK, and BAK alone have significant cytotoxic effects on human conjunctiva-derived cells and are associated with apoptosis. These effects likely result from BAK used as a preservative. IOP-lowering agents with alternative preservatives instead of BAK will most likely have fewer ocular surface adverse effects than agents containing BAK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 27 publications
5
78
1
1
Order By: Relevance
“…BAK exposure has been linked to OSD, 5-11 macular edema, 27 and reduced success of glaucoma filtering surgery. 28 BAK induces cytotoxic effects leading to apoptosis in conjunctival cell culture, 29,30 and several studies have demonstrated detrimental effects on both conjunctival and corneal cells in rabbit models. [9][10][11] This potential interaction between BAK and OSD is clinically relevant, as a recent study estimated that approximately 60% of glaucoma patients have symptoms of OSD.…”
Section: Discussionmentioning
confidence: 99%
“…BAK exposure has been linked to OSD, 5-11 macular edema, 27 and reduced success of glaucoma filtering surgery. 28 BAK induces cytotoxic effects leading to apoptosis in conjunctival cell culture, 29,30 and several studies have demonstrated detrimental effects on both conjunctival and corneal cells in rabbit models. [9][10][11] This potential interaction between BAK and OSD is clinically relevant, as a recent study estimated that approximately 60% of glaucoma patients have symptoms of OSD.…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic nature of most of them causes them to bind to the ocular tissues immediately after application and prolongs their action for as long as hundreds of hours. The half-time of BAK elimination from the eye surface is approximately 20 hours [13,14]. This is why we decided to use the long term culture model in this study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…This observation can be explained not only by the effect of active substances, but also by BAK action. Many other in vitro studies have shown that preservatives are cytotoxic, especially for the cells of the ocular surface: conjunctival and corneal epithelium and keratocytes [7,9,14,[16][17][18][19] but also for the deeper ocular tissues (fibroblast of Tenon's capsule, cells of lens epithelium and trabecular meshwork) [15,20]. Although the cytotoxic effect of BAK is well documented in patients [15] and on cultivated adherent cells, its influence on lymphocytes seems not to have been explored until this study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Furthermore, increased exposure to BAK-preserved eye drops prior to filtering surgery can have an adverse effect on surgical outcome 13 . The use of prostaglandin-containing eye drops without BAK has been shown to decrease epithelial permeability and preserve cell viability and membrane integrity 14,15 . Glaucoma requires long-term, chronic treatment.…”
Section: Introductionmentioning
confidence: 99%